Hadis Keutamaan Penuntut Ilmu: Analisis Parsial dan Simultan Riwayat Abu Darda’ dalam Sunan Abu Dawud - Nur Abdul Kholik Nugroho; Damanhuri Damanhuri (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Hadith on the Virtue of Knowledge Seeker: Partial and Simultaneous Analysis of Abu Darda' History in Sunan Abu DawudThe purpose of this study was to conduct a partial and simultaneous analysis of the exposure of hadith regarding the virtues of studying. The scope of this research is the main hadith narrated by Abu Darda' and take it out by Imam Abu Dawud. Data related to the hadith and the quality of the narrators were collected using the documentation method. Data analysis using content analysis method. Based on the partial analysis, it was found that this hadith is of authentic quality, because (1) all the narrators have the degree of tsiqah. (2) this hadith is muttasil. (3) this hadith does not contain syaz, because there is no contradiction with the naqli propositions of both the Qur'an and the hadith which have a higher quality sanad. (4) this hadith does not contain ‘illat, because there is no conflict with the aqli argument either with common sense, senses or science. Based on simultaneous analysis; This hadith has 4 tabi'. However, because the quality of the hadith is authentic, the existence of this tabi' hadith has no effect on improving its quality. As for the syahid, it turns out that there are 2 syahids, this means that the hadith was narrated through two friends, namely Abu Darda 'and Abu Hurairah